PENGARUH LOYALITAS PEGAWAI TERHADAP PROMOSI JABATAN PADA DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN KABUPATEN BIMA - Ryan Hidayat; Amirul Mukminin (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to determine and analyze the effect of significant employee loyalty to the promotion of positions at the Bima Regency Housing and Settlement Office. The type of research used is associative, with a sample of 68 respondents. The sampling technique used was purposive sampling. Data collection using a questionnaire with a Likert measurement scale. Data analysis methods used are validity test, reliability test, simple linear regression, simple correlation, determination test and t test (two parties). The results of this study conclude that employee loyalty has a significant influence on the promotion of position in the Department of Housing and Settlements of Bima Regency, where the t value of 0.425 is greater than the value of t table of 1.996 (0.425> 1.996) with a significance value of 0,000 less than 0.05 (0,000 <0.05).Keywords: Employee loyalty, promotion